LECTURA CA EXERCIȚIU DE ALTERITATE ÎN OPERA LUI JORGE LUIS BORGES - PILCHIN, Departamentul studii și cercetări, Biblioteca Municipală „B.P. Hasdeu”, Maria (BIBLIOPOLIS, 2020)
Today, during the war of all against all, the reading is more than an exercise in otherness. It is, as we want to believe, an exercise in conciliation and tolerance of the human being that is permanent becomes in a dialogue. In the era of Homo viator, we can establish the existence of an aesthetic of otherness, of a cultural catch of foreignness. We read it in political, cultural and literary discourses. One thing is certain, literature and reading as a „form of happiness” is already a Borgesian dimension that was established with time.